Automatic Route Planning of Robot Based On Plant Grow Optimization - Souresh, K; Saxena, A; Singh, K; Tomar, DS (International Journal of Computer Sciences and Engineering, 2019)
Robots can replace worker to finish a lot of complex works in complex environment. Recently, much research work has been done in the application of robots. To which robot navigation has become one of the most popular research field. The much emphasis is on programming of a complete, deterministic algorithm which is able to generate an optimum path in real time will and allow achieving a high level of autonomy. This means, for example, that you can read the newspaper when your car takes you to work on its own. In this paper we used the plant growth optimization algorithm for route selection in obstacle environment. The plant grow optimization algorithm is multi-objective optimization technique with multiple constraints such as growing of leaf and competition of branch. The system that needs to be optimized first "grows" from the root of a plant and then continues to "grow" until you find the optimal solution